2007
DOI: 10.1091/mbc.e06-07-0612
|View full text |Cite
|
Sign up to set email alerts
|

Atg27 Is Required for Autophagy-dependent Cycling of Atg9

Abstract: Autophagy is a catabolic pathway for the degradation of cytosolic proteins or organelles and is conserved among all eukaryotic cells. The hallmark of autophagy is the formation of double-membrane cytosolic vesicles, termed autophagosomes, which sequester cytoplasm; however, the mechanism of vesicle formation and the membrane source remain unclear. In the yeast Saccharomyces cerevisiae, selective autophagy mediates the delivery of specific cargos to the vacuole, the analog of the mammalian lysosome. The transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
4
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 41 publications
(68 reference statements)
10
143
4
5
Order By: Relevance
“…Atg9 localization to the PAS from the peripheral sites (referred to as anterograde transport) depends on Atg11, Atg23 and Atg27 [63,[87][88][89]. Return to the peripheral sites (retrograde movement) requires Atg1-Atg13, Atg2 and Atg18; PAS recruitment of the latter involves binding to PtdIns3P and thus necessitates the function of Atg14 and the class III PtdIns3K complex [63].…”
Section: Yeast Atg9mentioning
confidence: 99%
See 1 more Smart Citation
“…Atg9 localization to the PAS from the peripheral sites (referred to as anterograde transport) depends on Atg11, Atg23 and Atg27 [63,[87][88][89]. Return to the peripheral sites (retrograde movement) requires Atg1-Atg13, Atg2 and Atg18; PAS recruitment of the latter involves binding to PtdIns3P and thus necessitates the function of Atg14 and the class III PtdIns3K complex [63].…”
Section: Yeast Atg9mentioning
confidence: 99%
“…Similarly, no structural information has been published for the Atg11, Atg23 and Atg27 proteins, which are involved in Atg9 localization to the PAS [63,[87][88][89] (Figure 3). Atg18, together with Atg2, helps Atg9 cycle from the PAS to peripheral sites [63].…”
Section: Atg9 Complexmentioning
confidence: 99%
“…Because of the known role of Atg11, Atg23 and Atg27 in regulating Atg9 movement, 20,46 and based on our finding that the MKO strain expressing these proteins recapitulates the Atg9 localization phenotype seen with the mutant forms of Atg9, we hypothesized that the interaction of Atg9 with Atg23 and/or Atg27 might be affected in the Atg9 mutants (Atg11 is not essential for nonselective autophagy and the deletion of ATG11 has little effect on Phho8D60 activity 47 ). To test this hypothesis, we used the bimolecular fluorescence complementation (BiFC) assay.…”
Section: Phosphorylation Of S122 Regulates Atg9 Through Its Interactimentioning
confidence: 99%
“…18 Thus, Atg9 may move between these peripheral sites and the PAS, and earlier studies have suggested that this cycling of Atg9 is required for autophagosome formation, functioning in some manner to direct membrane to the expanding phagophore. 16,[19][20][21] In mammalian cells, ATG9 also displays dynamic cycling, moving between the trans-Golgi network and endosomes in response to nutritional changes. A subpopulation of ATG9 colocalizes with both LC3, a mammalian homolog of Atg8, and RAB7, a late endosomal protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation